Three‐year clinical outcomes after dual‐therapy COMBO stent placement: Insights from the REMEDEE registry. Issue 3 (18th December 2018) - Kalkman, Deborah N.; Kerkmeijer, Laura S.; Woudstra, Pier; Menown, Ian B. A.; Suryapranata, Harry; den Heijer, Peter; Iñiguez, Andrés; van 't Hof, Arnoud W. J.; Erglis, Andrejs; Arkenbout, Karin E.; Muller, Philippe; Koch, Karel T.; et al.
Abstract: Background: The bio‐engineered COMBO stent (OrbusNeich Medical BV, The Netherlands) is a dual‐therapy pro‐healing stent. This novel technology may allow a shorter duration of dual antiplatelet therapy (DAPT) after stenting. We present the first 3 year clinical outcomes of patients treated with COMBO stent. Methods and results: The prospective, multicenter, investigator‐initiated, all‐comers REMEDEE Registry evaluates clinical outcomes after COMBO stent treatment. A 1, 000 patients were enrolled between June 2013 and March 2014. Patients had a mean of 65 years ±11, 26% of the patients were females and 18% diabetics. More than 50% of patients presented with acute coronary syndrome, 60% of treated lesions were AHA/ACC lesion type B2 or C. Target lesion failure (TLF) at 3 year follow‐up occurred in 10.7% of patients (N = 105). The separate components cardiac death, target vessel myocardial infarction and target lesion revascularization occurred in 4.1%, 2.0%, and 7.1%, respectively of patients. Definite stent thrombosis (ST) was observed in 0.7% of all patients. At 3‐year follow‐up there were only 73 patients taking DAPT. Conclusions: At 3‐year follow‐up, patients treated with COMBO stent in the present large prospective all‐comers cohort, continue to show good clinical outcomes. Clinicaltrials.gov identifier: NCT01874002. Condensed abstract: The COMBO stent is a sirolimus‐eluting stent with a luminal anti‐CD34‐antibody layer, that binds endothelial progenitor cells. These cells can differentiate to endothelial cells and stimulate early endothelialization of the stent. The REMEDEE Registry is the first large, multicenter, prospective, cohort study evaluating the clinical outcomes of 1, 000 all‐comers patients treated with COMBO stent. Target lesion failure at 3 year follow‐up was 10.7% and the rate of definite ST was 0.7%.